Understanding history in Asia : c - d; Cannon, Tara. (Tokyo, Japan : Japan Publishing Industry Foundation for Culture, 2019)
The twentieth century has been called a century of war. Wars and col onization leave deep chasms between countries. In the case of Japan, th ese frictions have manifested themselves as historical issues. The hist ory since World War II has also been a history of trying to overcome th e hostility surrounding these issues. Since the end of the war there ha ve been various attempts at reconciliation, and indeed, periods in whic h Japan has enjoyed good relations with China and also with South Korea . Despite that, historical issues have overheated in the twenty-first c entury, and their effects may extend beyond Japan's relations with Chin a and South Korea to impact its relations with the United States, South east Asia, and Europe. --
The Japanese history textbook issue and "mutual trust" -- Official v isits to Yasukuni shrine -- The comfort women issue -- The Murayama sta tement -- Going beyond the century of war.
Originally published in Japan by Iwanami Shoten, 2015.
Includes bibliographical references (p. 237-267).
In English with Japanese title on colophon page.
Keywords: Japan -- Foreign relations -- 1945-; Japan -- Foreign relations -- China; China -- Foreign relations -- Japan; Japan -- Foreign relations -- Korea (South); Korea (South) -- Foreign relations -- Japan